Mistaken Asymptomatic Carinal Foreign Body in a Child. Issue 1 (January 2019) - Scerbo, Christina; Kilgar, Jennifer; Lim, Rodrick
Abstract : Abstract: Foreign body aspirations are commonly seen in emergency departments (EDs) worldwide, presenting with cough, dyspnea, wheeze, and decreased air entry. Chest radiographs are commonly utilized diagnostic tools to confirm foreign object aspiration. The following is a case report of a child who presented in the ED with a carinal push-pin aspiration and a lack of respiratory symptoms; an extremely rare ED presentation of foreign body aspirations masquerading as a foreign body ingestion. This attests to the importance of conducting a lateral chest radiograph for diagnostic purposes to accurately interpret an esophageal or tracheal foreign body placement.